The Arctic Journal
The Arctic Journal is developed by Greenlandic news organization Sermitsiaq.AG as a way to provide relevant news and journalism about the Arctic Region at the time when Arctic issues become increasingly important. In addition to being a source for news and journalism, the Arctic Journal will also focus on views and opinions from their readers.